Composition, richness, abundance, and association of anuran fauna with the flooded habitats in the Ariri district, eastern Amazon - Gonçalves Corrêa, Juliana; Ferreira França, Pedro; Sousa, Jackson Cleiton; Costa-Campos, Carlos Eduardo (Cuadernos de Herpetología, 2023)
Local inventories provide primary key information on diversity and distribution of species for conservation purposes. Here we describe the composition and conservation status of anuran fauna in flooded habitats eastern Amazon and evaluate to preference and the level of association of species with the flooded habitats in a poorly known area of the flooded forest present in the Ariri district, state of Amapá, North Brazil. Four nocturnal sampling events were carried out during the rainy season: beginning of the rainy season (March-May 2014 and December 2014-February 2015), mid rainy season (June-August 2014), and end of rainy season (September-November 2014), using visual encounter survey. We identified 29 anuran species. According to flooded habitat preference, the highest richness of species was found in high várzea (22 species, 75.9%, H’ = 3.091), and 16 species (55.2%) was recorded with high association with flooded habitats. Including all flooded habitats, a greater number of constant species were found, followed by accessory and accidental species. Species accumulation curve showed a tendency toward stabilization of species richness only in the end of rainy season. Our study provides important data on the local anuran fauna and the presence of species typical of flooded and non-flooded habitats demonstrates a certain degree of similarity between species composition, reinforcing the importance of flooded habitats for the preservation of anurans of the Amazonia Forest in north Brazil.